The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/s19173752
|View full text |Cite
|
Sign up to set email alerts
|

Payload for Contact Inspection Tasks with UAV Systems

Abstract: This paper presents a payload designed to perform semi-autonomous contact inspection tasks without any type of positioning system external to the UAV, such as a global navigation satellite system (GNSS) or motion capture system, making possible inspection in challenging GNSS- denied sites. This payload includes two LiDAR sensors which measure the distance between the UAV and the target structure and their inner orientation angle. The system uses this information to control the approaching of the UAV to the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Additionally, system ME magnitude is less than the 0.032 mm minimum single measurement resolution for this instrumentation. ME is superior to thin sample measurements reported in literature using commercial, UAV-targeted, instrumentation, which showed consistent errors of 0.6 mm across multiple readings [36]. An asymmetrical error distribution is described by the 5 th and 95 th percentile errors, demonstrating a slight bias towards undersized thickness measurements, which may be attributed to residual V-path effects.…”
Section: A Vertical Wall Thickness Measurementmentioning
confidence: 49%
See 1 more Smart Citation
“…Additionally, system ME magnitude is less than the 0.032 mm minimum single measurement resolution for this instrumentation. ME is superior to thin sample measurements reported in literature using commercial, UAV-targeted, instrumentation, which showed consistent errors of 0.6 mm across multiple readings [36]. An asymmetrical error distribution is described by the 5 th and 95 th percentile errors, demonstrating a slight bias towards undersized thickness measurements, which may be attributed to residual V-path effects.…”
Section: A Vertical Wall Thickness Measurementmentioning
confidence: 49%
“…Jarvis et al use a quadcopter to land a discrete Electro-Magnetic Acoustic Transducer (EMAT) sensor package atop a horizonal steel sheet and pipe section with success rates of 65% and 60%, respectively [35]. Ultrasonic measurement of a vertical metal plate is conducted in [36] using a large supporting outrigger to maintain contact. Updates to this system [37] apply horizontal thrust into the plate via two additional propellers, but do not grant full-actuation.…”
Section: A Related Workmentioning
confidence: 99%
“…Other UAV applications include: solar panel inspection [ 266 , 267 ]; power line and tower inspections [ 268 , 269 ]; water quality monitoring [ 270 ]; magnetic field mapping [ 271 ]; load transportation [ 272 , 273 ]; contact inspection tasks [ 274 ]; road safety and traffic monitoring [ 275 , 276 , 277 ]; aerial photography and cinematography [ 278 ]; entertainment and aerial shows [ 279 , 280 , 281 , 282 ]; firefighting [ 283 , 284 , 285 ].…”
Section: Research Challengesmentioning
confidence: 99%
“…The American Association of State Highway and Transportation Officials March 2016 survey found that 17 state Departments of Transportation had studied or used drones, whereas 16 states were either exploring UAV usage, assisting in the development of drone policies, or supporting drone research [27][28][29]. UAVs themselves cannot perform inspections independently, but can be used as a tool for bridge inspectors to view and assess bridge element conditions following the National Bridge Inspection Standard [30][31][32]. We believe that to achieve profits resulting from the automation of the image analysis process, it is also essential to automate the process of data acquisition, which is the drone flight route.…”
Section: Essentialsmentioning
confidence: 99%